2019
DOI: 10.31925/farmacia.2019.2.5
|View full text |Cite
|
Sign up to set email alerts
|

Possible Molecular Mechanisms and Pathways Involved in Bh3 Mimetic Activity of Alpha-Lipoic Acid on Human Colon Cancer Cell Line

Abstract: Alpha-lipoic acid (ALA), a naturally-occurring antioxidant, inhibits proliferation and induces apoptosis in various cancer cell lines without effects on normal non-transformed cells. The aim of this study was to examine the effects of alpha-lipoic acid (ALA), alone and combined with 5-fluorouracil (5-FU), on Bcl-2/Bax expression in human colon cancer Caco-2 cell line as well as to investigate possible molecular mechanisms and pathways involved in ALA-mediated effects. In the present study ALA and 5-FU showed a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 48 publications
0
4
0
Order By: Relevance
“…More than 50% of all CRC patients will develop metastases during the course of the disease, either synchronous or metachronous [14]. Metastatic disease has a poor prognosis, with 5-year relative survival rates only reaching 13.1% [6]. The clinical outcomes have greatly improved in stage IV patients, with a median overall survival (OS) reaching 30 months, due to better management that uses a "treatment continuum".…”
Section: Introductionmentioning
confidence: 99%
“…More than 50% of all CRC patients will develop metastases during the course of the disease, either synchronous or metachronous [14]. Metastatic disease has a poor prognosis, with 5-year relative survival rates only reaching 13.1% [6]. The clinical outcomes have greatly improved in stage IV patients, with a median overall survival (OS) reaching 30 months, due to better management that uses a "treatment continuum".…”
Section: Introductionmentioning
confidence: 99%
“…To evaluate the pharmacological character of compounds, the Lipinski rules and the Veber rules (bioavailability) were applied [17,18]. The Lipinski's rule of five refers to the possibility of drug-like features of small molecules if the following criteria are respected: (i) no more than 5 hydrogen bond donors in the structure; (ii) no more than 10 hydrogen bond acceptors in the structure; (iii) molecular mass less than 500 Daltons; (iv) octanol-water partition coefficient (MlogP) does not exceed 5.…”
Section: Drug-like Character and Bioavailability Evaluation Of 25-disubstituted 134-oxadiazole Compounds 1a-d P7c3 P7c3-a20 And P7c3-s243mentioning
confidence: 99%
“…The Lipinski's rule of five refers to the possibility of drug-like features of small molecules if the following criteria are respected: (i) no more than 5 hydrogen bond donors in the structure; (ii) no more than 10 hydrogen bond acceptors in the structure; (iii) molecular mass less than 500 Daltons; (iv) octanol-water partition coefficient (MlogP) does not exceed 5. Veber rule imposed for a good bioavailability as (i) 10 or fewer rotatable bonds in structure, (ii) less than 12 hydrogen bond donors or acceptors in total in the structure; (iii) topological polar surface area (TPSA) less than 140 Å 2 [17]. To calculate the Lipinski and Veber rules, the SMILES file of the molecules (Table I) was loaded into the ExPASy Bioinformatics Resource Portal and the cheminformatics database Molinspiration [19,20].…”
Section: Drug-like Character and Bioavailability Evaluation Of 25-disubstituted 134-oxadiazole Compounds 1a-d P7c3 P7c3-a20 And P7c3-s243mentioning
confidence: 99%
“…Previous studies have collectively suggested ALA as a potent inhibitor of MMP-2 and MMP-9 activities, which reduces the invasion of various cancer cells [24][25][26]. ALA also successfully induces cancer cell death by increasing the expression of proapoptotic genes such as Bcl-2-associated X protein (Bax) and decreasing the expression of the primary antiapoptotic gene, B-cell lymphoma 2 (Bcl2) [27,28].…”
Section: Introductionmentioning
confidence: 99%